Design features and operating experience of experimental fast reactors - Rinejski, A.; Stanculescu, A.; Yanev, Y.; Monti, S. (IAEA nuclear energy series,, 2013)
"Growing energy needs and concern for the environment drive the demand for large scale and low impact energy sources. Therefore, national and international research on fast reactor technology is increasing. As a part of the IAEA efforts for knowledge preservation and data retrieval, this publication compiles and documents significant aspects of fast reactor engineering development and experience. Its focus is on research and developing activities, experience with experimental facilities and properties, and criteria for comparison and choice of liquid metal coolants. The introductory part includes the history, the state of the art and an overview of fast reactor cooling, heat transport and heat conversion systems development. This is followed by basic information on liquid metal coolants and design features. The publication concludes with a summary which identifies the progress achieved and issues to be resolved in sodium and heavy metal coolant technology"--Publisher's description.